2016
DOI: 10.1038/srep34588
|View full text |Cite
|
Sign up to set email alerts
|

Co-acclimation of bacterial communities under stresses of hydrocarbons with different structures

Abstract: Crude oil is a complex mixture of hydrocarbons with different structures; its components vary in bioavailability and toxicity. It is important to understand how bacterial communities response to different hydrocarbons and their co-acclimation in the process of degradation. In this study, microcosms with the addition of structurally different hydrocarbons were setup to investigate the successions of bacterial communities and the interactions between different bacterial taxa. Hydrocarbons were effectively degrad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
34
1
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 58 publications
3
34
1
3
Order By: Relevance
“…In treatments amended with digestate also an increase of taxa containing recognized TPH degraders was observed. In S1 soil for treatments CDA and CDBI Mycobacterium species were still present, however new dominant genera appeared including Arenimonas which was previously observed in hydrocarbon degrading cultures and associated with oil degradation (Reyes-Sosa et al, 2018;Wang et al, 2016), Arthrobacter (for CDA only) able to degrade crude oil components (Reyes-Sosa et al, 2018) and Thermomonas which was observed in microbial communities under intensive oil degradation (Al-Kharusi et al, 2016).…”
Section: Bacterial Diversity On the Genus Levelmentioning
confidence: 70%
See 1 more Smart Citation
“…In treatments amended with digestate also an increase of taxa containing recognized TPH degraders was observed. In S1 soil for treatments CDA and CDBI Mycobacterium species were still present, however new dominant genera appeared including Arenimonas which was previously observed in hydrocarbon degrading cultures and associated with oil degradation (Reyes-Sosa et al, 2018;Wang et al, 2016), Arthrobacter (for CDA only) able to degrade crude oil components (Reyes-Sosa et al, 2018) and Thermomonas which was observed in microbial communities under intensive oil degradation (Al-Kharusi et al, 2016).…”
Section: Bacterial Diversity On the Genus Levelmentioning
confidence: 70%
“…This genus was not previously assigned to TPH degradation activity and surprisingly it was linked with mercury resistance (Pepi et al, 2011). Among other top genera, Acinetobacter species were shown to be able to use alkanes as a carbon and energy source and possess alkB genes (Liu et al, 2011;Nie et al, 2014;Wang et al, 2011), while Mycobacterium was previously observed to catalyse different reaction and express wide range of catabolic genes including alkB genes (Nie et al, 2014;Wang et al, 2016). In treatments amended with digestate also an increase of taxa containing recognized TPH degraders was observed.…”
Section: Bacterial Diversity On the Genus Levelmentioning
confidence: 93%
“…Muricauda is a common heterotrophic marine bacterium, with several representative members isolated (Hwang et al ). Their contribution to the degradation of aliphatic hydrocarbons (JimĂ©nez et al ) and pristane (Wang et al ) have been reported, as well as their preference for sub products from hydrocarbon degradation (Bruns et al ). However, their relationships or dependence with other taxa are still unknown.…”
Section: Discussionmentioning
confidence: 99%
“…The biofilm architecture is structurally supported by the extracellular polymeric substances (EPS) produced by the community members, which provide a number of advantages for the community, such as stability, cell–cell proximity favouring interactions and genetic exchange (Madsen et al ., ; Ren et al ., ), protection against stressors and predators, passive sorption of solutes, amongst other benefits. In fact, in hydrocarbon‐polluted sites, environmental bacterial isolates often only degrade a narrow range of PAHs, and cooperative processes involving a consortium of strains with complementary capacities are frequently observed (Bouchez et al ., ; Wang et al ., ).…”
Section: Introductionmentioning
confidence: 97%